ANALISIS KINERJA KEUANGAN BERBASIS ECONOMIC VALUE ADDED (EVA) PADA PT. BANK SULUTGO - Sondakh, Marcelino; Mangindaan, J. V.; Keles, Dantje (Sam Ratulangi University, 2017)
The purpose of this study is to find out how much Economic Value Addedgenerated by PT. Bank SULUTGO in 2014-2016. It is known that PT. Bank SULUTGOis a regional bank of North Sulawesi and Gorontalo which owns shares from variousregions and several companies. It is known that the capital annually PT. BankSULUTGO in 2014-2016 always increases. But with the increase in capital whether ithas made the company able to improve the performance of the company or increase therevenue of the company so as to be able to distribute the fair share of the results to theshareholders of the company. The purpose of this study is